A Novel Test of Pure Irrelevance-Induced Blindness - Büsel, Christian; Ditye, Thomas; Muttenthaler, Lukas; Ansorge, Ulrich (Frontiers in Psychology, 2019)
Load theory claims that bottom-up attention is possible under conditions of low perceptual load but not high perceptual load. At variance with this claim, a recent one-trial study showed that under low load, with only two colors in the display – a ring and a disk –, an instruction to process only one of the two stimuli led to better memory performance for the color of the relevant than of the irrelevant stimulus. Control experiments showed that if instructed to pay attention to both objects, participants were able to memorize both colors. Thus, stimulus irrelevance diminished the likelihood of memory for a color stimulus under low perceptual-load conditions. Yet, we noted less than optimal design features in that prior study: a lack of more implicit priming measures of memory or attention and an interval between color stimulus presentation and memory test that probably exceeded 500 ms. We took care of these problems in the current one-trial study by improving the retrieval displays while leaving the encoding displays as in the original study and found that the results only partly replicated prior findings. In particular, there was no evidence of irrelevance-induced blindness under conditions in which a ring was designated as relevant, surrounding an irrelevant disk. However, a continuously cumulative meta-analysis across past and present experiments showed that our results do not refute the irrelevance-induced effects entirely. We conclude with recommendations for future tests of load theory.